1987
DOI: 10.3171/jns.1987.67.2.0258
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-antitrypsin in human brain tumors

Abstract: This study was undertaken to confirm the presence of alpha-1-antitrypsin (alpha 1-AT) in human brain tumors and to attempt to elucidate its significance. Seventy-seven consecutive unselected patients with various brain tumors were entered in this study. The alpha 1-AT and alpha 2-macroglobulin contents of the tumor extracts were qualitatively assessed by Ouchterlony immunodiffusion techniques. Plasminogen activator (PA) activity was assayed electrophoretically on sodium dodecyl sulfate gels. The patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
(13 reference statements)
1
17
0
Order By: Relevance
“…6) Serum level of A1AT was found to be increased in malignant diseases such as: Gastrointestinal cancer, prostate cancer, brain tumors, biliary tract cancer, pancreatic adenocarcinoma and breast cancer. [7][8][9][10][11][12] A significant correlation between A1AT serum levels and cancer stages was also observed. 7,13) An imbalance in the ratio between the levels of particular protease and protease inhibitor found to be responsible for the increase in tumor formation potential.…”
Section: Introductionmentioning
confidence: 99%
“…6) Serum level of A1AT was found to be increased in malignant diseases such as: Gastrointestinal cancer, prostate cancer, brain tumors, biliary tract cancer, pancreatic adenocarcinoma and breast cancer. [7][8][9][10][11][12] A significant correlation between A1AT serum levels and cancer stages was also observed. 7,13) An imbalance in the ratio between the levels of particular protease and protease inhibitor found to be responsible for the increase in tumor formation potential.…”
Section: Introductionmentioning
confidence: 99%
“…serine proteases, in tumour cells is associated with malignant potency (Mignatti et al, 1986;Tryggvason et al, 1987;Zucker, 1988 Ades et al, 1982). Sawaya et al (1987) suggested that AAT produced in brain tumours may protect against inflammatory activity of the host. Therefore, AAT in tumour cells may have the capacity to promote tumour development and metastasis by incapacitating host anti-tumour defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…AAT is expressed not only in normal livers but also in other normal tissues such as the lung, gall bladder, pancreas, and the gastrointestinal tract (Tuttle & Jones, 1975;Ray et al, 1978;Kittas et al, 1982a;Geboes et al, 1982;Tahara et al, 1984;Aroni et al, 1984). Moreover, AAT has also been demonstrated in several neoplasms including carcinomas, mesenchymal tumours, hemopoietic and brain tumours (Reintoft & Hargerstrand, 1979;Kittas et al, 1982b;Glasgow et al, 1982;Aroni et al, 1984;Tahara et al, 1984;Krugliak et al, 1986;Wittekind et al, 1986;Sawaya et al, 1987;Soini & Miettinen, 1989;Kataoka et al, 1989;Perlmutter et al, 1989;Karashima et al, 1990). The presence of AAT in tumour cells is now considered to be due to its production by tumour cells themselves (Glasgow et al, 1982;Perlmutter et al, 1989;Kataoka et al, 1989).…”
mentioning
confidence: 99%
“…AAT augments in the serum of gastrointestinal [15], prostate [16], brain [17] as well as biliary tract cancer [18] patients. Also reports indicate increased serum AAT in pancreatic adenocarcinoma [19], breast tumors [20], and esophageal cancer [21].…”
Section: Aat a Response To Malignancy And Inflammationmentioning
confidence: 99%